Internet-based acceptance and commitment therapy programme ‘Happiness Mom’ for well-being: a protocol for a randomised controlled trial - Yuka Kobayashi; Norito Kawakami; Kotaro Imamura; Yuki Sekiya; Natsu Sasaki; Kanami Tsuno; Kazuhiro Watanabe; Daisuke Nishi (BMJ Open)
Introduction This randomised controlled trial (RCT) aims to examine the effects of an internet-delivered acceptance and commitment therapy (iACT) programme (‘Happiness Mom’) on the psychological well-being of working mothers.Methods and analysis The target population of the RCT will be employed mothers with at least one preschool child. Participants who fulfil the study’s eligibility criteria will be randomly assigned either to an iACT intervention group (n=200) or to a wait-list control group (n=200). Participants in the intervention groups will be asked to complete the programme within 12 weeks of the baseline survey. The intervention programme contains eight modules based on ACT. Primary outcomes are six components of psychological well-being, based on Ryff’s theory. Secondary outcomes are intention to leave their job, work engagement, work performance, sick leave days, psychological distress, euthymia, positive emotions, job and life satisfaction, social support and parental burn-out.Ethics and dissemination Ethical approval for this study has been obtained from the Research Ethics Review Board of Graduate School of Medicine, the University of Tokyo (No. 2019134NI). If the intervention programmes are found to be significantly beneficial, the programmes can be made available for all working mothers with preschool children in Japan.Discussion This study will contribute to the development of an internet-based self-care programme that is effective, feasible, low cost and accessible to improve the well-being of working mothers.Trial registration number UMIN000039918.